Clinical decision support system for clinical nurses’ decision-making on nurse-to-patient assignment: a scoping review protocol - Hyunjeong Kwon; Dayeon Lee (BMJ Open)
Introduction Optimal nurse-to-patient assignment plays a crucial role in healthcare delivery, with direct implications for patient outcomes and the workloads of nursing staff. However, this process is highly intricate, involving a multitude of factors that must be carefully considered. The application of a clinical decision support system (CDSS) to support nursing decision-making can have a positive impact not only on patient outcomes but also on nursing efficiency. This scoping review aims to explore the implementation of CDSS in the decision process of optimal nurse-patient assignment (NPA).Methods and analysis This scoping review will follow a stage of the Arksey and O’Malley framework. It will also be based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews’ (PRISMA-ScR) guidelines. The research primarily aims to identify studies’ findings on applying CDSSs in the NPA process. Hence, academic and grey literature articles from six international bibliographic databases (ie, MEDLINE via PubMed, EMBASE via Ovid, CINAHL via EBSCOhost, IEEE Xplore, Scopus, ProQuest Dissertations and Theses Global) will be considered, where search strategies will be tailored to each database. The literature search will be conducted in February 2024, and the identified studies will be independently screened by two primary reviewers. After extracting data, the qualitative data will be analysed thematically, and the quantitative data will be subjected to descriptive statistics. The research is scheduled to conclude in December 2024.Ethics and dissemination Ethical approval is not required as primary data will not be collected in this study. The findings of this study will be disseminated through peer-reviewed publications and conference presentations.